The Influence of Business Capital on The Income of Culinary Traders on The Cempae Tanggul in Parepare City (Islamic Economic Analysis) - Padila, Nur Isma; Umaima, Umaima; Sumirah, Sumirah (OECONOMICUS Journal of Economics, 2024)
Capital is one of the production factors that affect the level of income. This study aims to determine how well the business capital and income of culinary traders on the Cempae Embankment in Parepare City, whether there is a positive and significant influence between business capital and income, and to determine the effect of business capital on the income of culinary traders on the Cempae Embankment in Parepare City. The approach used in this research is an associative approach, with the type of field research and the method used is quantitative method, especially descriptive quantitative. This study examines the effect of business capital on the income of culinary traders on the Cempae Embankment, Parepare City. Using an associative approach and descriptive quantitative methods, the research lasted 31 days. The results showed: 1. Business capital and trader income are in the good category. 2. There is a positive and significant relationship between business capital and income, with a moderate correlation level. 3. Business capital affects income, where every additional 1% of business capital increases income by 0.025. 4. Business capital affects 50.6% of income, while 49.4% is influenced by other factors outside this study